Constructing a High‐Strength Solid Electrolyte Layer by In Vivo Alloying with Aluminum for an Ultrahigh‐Rate Lithium Metal Anode. (13th December 2019) - Lu, Ziyang; Li, Wantang; Long, Yu; Liang, Jiachen; Liang, Qinghua; Wu, Shichao; Tao, Ying; Weng, Zhe; Lv, Wei; Yang, Quan‐Hong
Abstract: The serious safety issues caused by uncontrollable lithium (Li) dendrite growth, especially at high current densities, seriously hamper the rapid charging of Li metal‐based batteries. Here, the construction of Al–Li alloy/LiCl‐based Li anode (ALA/Li anode) is reported by displacement and alloying reaction between an AlCl3 ‐ionic liquid and a Li foil. This layer not only has high ion‐conductivity and good electron resistivity but also much improved mechanical strength (776 MPa) as well as good flexibility compared to a common solid electrolyte interphase layer (585 MPa). The high mechanical strength of the Al–Li alloy interlayer effectively eliminates volume expansion and dendrite growth in Li metal batteries, so that the ALA/Li anode achieves superior cycling for 1600 h (2.0 mA cm −2 ) and 1000 cycles at an ultrahigh current density (20 mA cm −2 ) without dendrite formation in symmetric batteries. In lithium–sulfur batteries, the dense alloy layer prevents direct contact between polysulfides and Li metal, inhibiting the shuttle effect and electrolyte decomposition. Long cycling performance is achieved even at a high current density (4 C) and a low electrolyte/sulfur (6.0 µL mg −1 ). This easy fabrication process provides a strategy to realize reliable safety during the rapid charging of Li‐metal batteries. Abstract : The universal Al–Li alloy‐based layer is demonstrated to be highly effective for stabilizing the lithium metal anode at an ultrahigh current density. The high strength layer not only inhibits the growth of lithium dendrites but also prevents the parasitic reactions of Li with the liquid electrolyte and polysulfides.